Early-Adulthood Economic Experiences and the Formation of Democratic Support. Issue 2 (12th April 2023) - Krishnarajan, Suthan; Doucette, Jonathan; Andersen, David
Abstract: Do economic experiences early in life affect regime support later in life? Effects of recent economic performance on regime support are extensively studied, but lasting effects of individual-level economic experiences across the lifespan remain unexplored. We argue that in democracies and autocracies alike, economic experiences in early adulthood (that is, age eighteen to twenty-eight) are wired into people's memories and become important cues for their democratic support later in life. Having lived in a well-performing economy in a democracy increases democratic support throughout most of people's lives, whereas having lived in a well-performing economy in an autocracy decreases democratic support throughout most of people's lives. Using extensive survey data on support for democracy covering ninety-seven countries from 1994 to 2015, we find support for these propositions, demonstrating that economic experiences in early adulthood, conditional on the regime in place at the time, have strong, robust and lasting effects on democratic support.